I have a dream - King, Martin Luther, Jr., 1929-1968; Nelson, Kadir (New York : Schwartz & Wade Books, 2012)
Presents the text of the famous speech given on the National Mall in Washington, D.C. by Martin Luther King, Jr., complemented by paintings illustrating the ideals the civil rights leader described.
Keywords: African Americans -- Civil rights -- Juvenile literature; Civil rights movements -- United States -- History -- Juvenile literature; Audiobooks; African Americans -- Civil rights; Civil rights movements -- United States -- History; African Americans -- Civil rights; Civil rights demonstrations -- United States -- History; Children's audiobooks; Audiobooks